iRead4Skills @ IberSPEECH 2024: Project presentation and developments for the Portuguese language - J. Baptista; Ribeiro, E.; Mamede, N. (IberSPEECH 2024, 2024)
The iRead4Skills project aims to enhance adult literacy and essential skills by merging technology and culture. It addresses the needs of adult learners, particularly those with low literacy skills, by providing an intelligent system that evaluates text complexity and suggests readings suited to individual levels. This open-access system supports multilingual environments, offering resources in languages like Portuguese, Spanish, and French. The project innovates by using end-user input to develop new text complexity measures, thus aligning learning tools more closely with real-world literacy needs. It also emphasizes the role of technology, especially in the area of NLP, in tailoring educational materials for trainers and learners. Through collaboration with various stakeholders -- including universities, government bodies, and research institutions -- the project aims to inform policymakers and educators about ways to improve workforce skills and foster lifelong learning across Europe.